El homicidio agravado del artículo 324 numeral 5o.: "Valiéndose de la actividad de imputable" - Amaya Castrillón, Juan Carlos (Estudios de Derecho, 1997)
El homicidio agravado del artículo 324 numeral 5o.: "Valiéndose de la actividad de imputable"